Pemaknaan Etika Jurnalisme Warga oleh Jurnalis Warga Tempo Witness di Wilayah Jawa Tengah - Soraya, Nadia Ayu; Gumilar, Gumgum; Al-Faqih, M Zein (Jurnal Kajian Jurnalisme, 2023)
Awareness of the importance of conveying phenomena around, in line with the skills in utilizing information technology to form citizens like journalists. The ease with which citizens become like journalists raises the intention of citizens to uphold the truth by becoming citizen journalists. However, various applications of citizen journalism ethics that are difficult to practice are actually a challenge. It even creates a temptation to apply citizen journalism ethics. These challenges and temptations diverted their initial intentions as citizen journalists. They do not obey the code of ethics that applies when conducting journalistic activities. This study aims to explore the meaning of the ethics of citizen journalism by citizen journalists of Tempo Witness in the Central Java region, which is the area with the highest intensity of sending news reports. Qualitative methods, phenomenological approaches, and symbolic interaction theory function to explore the motives, experiences, and agreements of citizen journalists in applying the ethics of citizen journalism. The results showed that the three informants interpreted the ethical aspects of citizen journalism well, they maintained good manners and maintained the quality of news reports. However, two of the three informants did not apply the ethics of citizen journalism by accepting gifts from the informants, in the form of envelopes and lunches.